The influence of mobile communication technologies in long-term e-learning - Susimenko, Elena; Gura, Alena; Rakhmanova, Alsu; Butylchenko, Olga (Institute of Advanced Engineering and Science, 2025)
Communicative abilities constitute a crucial element of successful learning and interaction. The psychological impact of the prolonged lack of face-to-face contact with the peer audience and teachers typically remains an unresolved problem, despite the availability of appropriate online learning methodologies and technical tools. This study aims to ascertain a quantitative assessment of social maladjustment and a reduction in the level of communicative competence resulting from prolonged distance learning and the use of mobile devices in communication. The research employs a quantitative approach and is based on a survey of students who participated in eight socio-psychological training sessions (A-trainings). The training sessions are oriented towards refining the personal qualities of individuals and facilitating their adaptation to the fluctuating conditions of learning environments. The analysis of pre-and post-training results was compared with the results of the control group. The research findings indicate a positive impact of socio-psychological training on the enhancement of communicative skills and emotional well-being of students.